2011
DOI: 10.1139/p11-035
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics in weakly polar nematic liquid crystal doped with dye

Abstract: Our intention in the present work is to find out the role of dye in the molecular orientation of the weakly polar nematic liquid crystal D6AOB. The doping of a dye introduces a disturbance in the molecular arrangement of the nematic liquid crystal molecules. However, this disturbance is found to be sensitive to the concentration of the dye dispersed in the nematic liquid crystal. It is found that orientation in the dyed nematic liquid crystal is less ordered than the orientation in the pure nematic liquid crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The generated electric field would be localized but it would have some effect on the polarization though it will be a feeble one. Thus, the value of average dielectric permittivity decreases with increase in the concentration of the dopant .…”
Section: Resultsmentioning
confidence: 97%
“…The generated electric field would be localized but it would have some effect on the polarization though it will be a feeble one. Thus, the value of average dielectric permittivity decreases with increase in the concentration of the dopant .…”
Section: Resultsmentioning
confidence: 97%
“…Physical properties of LC such as optical and dielectric parameters, rotational viscosity, temporal characteristics, molecular dynamics, etc. [76,119,120,123,[144][145][146][147][148][149].…”
Section: Hysteresis Effectmentioning
confidence: 99%
“…Many reports have been presented to study these weakly polar nematic LCs which explain the dielectric properties with the help of dynamics of molecule. [7,8] Oka et al have done the comparative study of weakly polar and non-polar NLCs. They suggested that the strength of dipole moment has little influence on the liquid crystalline properties.…”
Section: Introductionmentioning
confidence: 99%